2019
DOI: 10.1186/s43055-019-0074-z
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transhepatic hemodialysis catheters in chronic hemodialysis patients: technique, functional outcome, and complications from a large population study

Abstract: Background: Chronic renal failure is one of the main health problems in Egypt. Arterio-venous fistulas, grafts, as well as conventional sites for placement of the dialysis catheters are liable to thrombosis; stenosis, and occlusions, so alternative routes are considered as life-saving ways in such cases. Transhepatic permcath is one of the new and up to date methods for inferior vena cava and right atrium catheterization. Few studies with rather limited nomber are available to evaluate transhepatic permcath. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
0
7
3
Order By: Relevance
“…Stavropoulos et al 13 and Smith et al 14 attributed the high incidence of thrombosis in THC to the shorter trans-vascular distance traversed by the catheter to meet IVC probably influencing the flow in that segment. The observed catheter migration rate (0.12 per 100 catheter days) of THCs in this study is lower compared to previously published studies [13][14][15][16][17] As outlined seen in Table 3, another complication observed is the occurrence of infection. The infection rate for this study (0.046 per 100 catheter days) was lower compared to infection rates in previous studies.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…Stavropoulos et al 13 and Smith et al 14 attributed the high incidence of thrombosis in THC to the shorter trans-vascular distance traversed by the catheter to meet IVC probably influencing the flow in that segment. The observed catheter migration rate (0.12 per 100 catheter days) of THCs in this study is lower compared to previously published studies [13][14][15][16][17] As outlined seen in Table 3, another complication observed is the occurrence of infection. The infection rate for this study (0.046 per 100 catheter days) was lower compared to infection rates in previous studies.…”
Section: Discussioncontrasting
confidence: 74%
“…The infection rate for this study (0.046 per 100 catheter days) was lower compared to infection rates in previous studies. [13][14][15][16][17] Catheter-related bloodstream infection also occurs in THC as it does in other types of catheters. 20 Migration is one of the complications identified in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations